Impact of wetting agents, time of day and periodic energy dosing strategy on the efficacy of hot water for weed control. (6th June 2016) - De Cauwer, B; De Keyser, A; Biesemans, N; Claerhout, S; Reheul, D
Summary: To further increase the cost‐effectiveness and sustainability of hot water weed control, the further optimisation of hot water efficacy is needed. Therefore, three dose–response experiments were carried out to evaluate the impact of wetting agents (an ethoxylated triglyceride, an esterified rapeseed oil and a liquid linseed oil‐based soap), time of day (2, 4, 6, 8, 10 and 12 h after sunrise) and treatment frequency (1–6 treatments in a 12 week period) on the hot water sensitivity of prevalent weed species ( Lolium perenne, Festuca rubra, Taraxacum officinale and Plantago major ) on public pavements. Generally, wetting agents did not improve hot water sensitivity. Taraxacum officinale with large planophile leaves showed a higher sensitivity than grasses with an erectophile growth habit. Festuca rubra was more sensitive than L. perenne due to its high leaf dry matter content. The plant species were most sensitive to hot water in the afternoon. This variation in sensitivity during the day was related to the variation in leaf thickness and dry matter content. In general, hot water weed control was highly efficient when conducted four times in a 12 week period at an energy dose of 589 kJ m −2 .